LMPA Regulates Lesion Mimic Leaf and Panicle Development Through ROS-Induced PCD in Rice - Hu, Peng; Tan, Yiqing; Wen, Yi; Fang, Yunxia; Wang, Yueying; Wu, Hao; Wang, Junge; Wu, Kaixiong; Chai, Bingze; Zhu, Li; Zhang, Guangheng; Gao, Zhenyu; et al. (Frontiers in Plant Science, 2022)
Leaf and panicle are important nutrient and yield organs in rice, respectively. Although several genes controlling lesion mimic leaf and panicle abortion have been identified, a few studies have reported the involvement of a single gene in the production of both the traits. In this study, we characterized a panicle abortion mutant, lesion mimic leaf and panicle apical abortion (lmpa), which exhibits lesions on the leaf and causes degeneration of apical spikelets. Molecular cloning revealed that LMPA encodes a proton pump ATPase protein that is localized in the plasma membrane and is highly expressed in leaves and panicles. The analysis of promoter activity showed that the insertion of a fragment in the promoter of lmpa caused a decrease in the transcription level. Cellular and histochemistry analysis indicated that the ROS accumulated and cell death occurred in lmpa. Moreover, physiological experiments revealed that lmpa was more sensitive to high temperatures and salt stress conditions. These results provide a better understanding of the role of LMPA in panicle development and lesion mimic formation by regulating ROS homeostasis.